Harmonization of Theft Prevention Regulations Digital Personal Data in Banking Institutions: Perspective Cybercrime Sniffing - Noviasari, Ryska; Yuspin, Wardah; Budiono, Arief (Faculty of Law, Universitas Pekalongan, 2024)
This research aims to find out how to harmonize relevant applicable laws and regulations in Cybercrime Sniffing and to analyze the protection provided by law to deal with sniffing cases. This research uses normative research methods. The results of this research are: first, crime regulation sniffing in hacking M Banking via the WhatsApp application, which has been regulated in Article 51 paragraph (2) of the ITE Law and its amendments and Article 67 paragraph (1) of the PDP Law has differences in the aspect of criminal sanctions and/or fines, where the sanctions in the ITE Law and its amendments are more the severity of the sanctions contained in the PDP Law. Refers to the principle of preference, namely the principle of a particular law derogating from the general law and based on teleological/sociological interpretation by looking at the purpose of establishing the law, it can be concluded that in cases of criminal acts in the form of sniffing In the hacking of M Banking via the WhatsApp application, because it relates to personal data breaches, what applies is the provisions of Article 67 paragraph (1) of the PDP Law, because the PDP Law is a regulation that more specifically regulates personal data breaches, so the ITE Law and its amendments are as follows: more general settings should be ruled out. The protection provided by the Act to deal with cases of sniffing M-Banking hacking via the WhatsApp application is regulated by criminal sanctions in Article 67 paragraph (1) of the PDP Law, which can be interpreted to mean that the PDP Law provides criminal sanctions and/or fines to all parties, including banks if there is loss resulting from these actions. Sniffing has implications for harming the victim.